Correlation Analysis between Serum Vitamin D Levels and Lower Extremity Macrovascular Complications in Individuals with Type 2 Diabetes Mellitus. (28th November 2019) - Yang, Mengxue; Liu, Jun; Zhou, Xue; Ding, Heyuan; Xu, Jie; Yang, Bo; Sun, Bowen; Xiao, Dandan; Yu, Jie; Gong, Qihai
Abstract : The correlation between serum 25-hydroxy vitamin D (25(OH)D) levels and lower extremity atherosclerotic disease and the predictive value of 25(OH)D for early-stage lower extremity atherosclerotic disease in patients with type 2 diabetes mellitus (T2DM) were explored. In total, 620 subjects (590 T2DM patients and 30 healthy subjects) completed a questionnaire. All subjects were divided into four groups according to serum 25(OH)D concentration quartile: Q1 (<12.18 ng/ml), Q2 (12.18 20.65 ng/ml), Q3 (20.65 31.97 ng/ml), and Q4 (>31.97 ng/ml). Participants were also divided into four groups based on the degree of lower extremity arteriostenosis: A1 (T2DM), A2 (T2DM with mild lower extremity vascular lesions (LEVL)), A3 (T2DM with moderate LEVL), and A4 (T2DM with severe LEVL). The incidence of lower extremity artery plaque was significantly higher in groups Q1 and Q2 than in group Q4 (both P < 0.05 ). The concentration of 25(OH)D was significantly lower in group A4 than in groups A1 and A2. Pearson correlation analysis revealed that the degree of lower extremity vascular stenosis was positively correlated with age, smoking, and HbA1c, CRP, and LDL-C levels and negatively correlated with 25(OH)D concentrations. Logistic regression analysis demonstrated that 25(OH)D concentrations exerted a protective effect against LEVL in T2DM patients. Serum 25(OH)D concentrations may be correlated with the incidence of macrovascular disease in T2DM patients. A low serum 25(OH)D concentration is an independent risk factor for lower extremity vascular pathological changes and acts as a prognostic index for lower extremity atherosclerotic disease.